Fatty acid synthase plays a positive role in shrimp immune responses against Vibrio parahaemolyticus infection. Issue 60 (January 2017) - Zuo, Hongliang; Gao, Jiefeng; Yuan, Jia; Deng, Hengwei; Yang, Linwei; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: Fatty acid synthase (FAS) is an important enzyme that catalyzes the synthesis of fatty acids. In this study, the role of the FAS gene from pacific white shrimp Litopenaeus vannamei (LvFAS) in immune responses against Vibrio parahaemolyticus infection was studied. The expression of LvFAS could be up-regulated upon infection of V. parahaemolyticus and stimulation of lipopolysaccharide and poly (I:C). The promoter of LvFAS was predicted to harbor a NF-κB binding site and dual-luciferase reporter assays demonstrated that the NF-κB family proteins Relish, sRelish and Dorsal could activate the transcription of LvFAS. After knockdown of LvFAS expression using RNAi strategy, both the mortality of V. parahaemolyticus infected shrimps and the bacterial load in shrimp tissues were significantly increased. Meanwhile, the expression of many immune-responsive genes, such as antimicrobial peptides, C-type lectins (CTLs), lysozyme and hemolin, was down-regulated. These suggested that LvFAS could play a positive role in anti - V. parahaemolyticus responses in shrimp. To our knowledge, this is the first study that investigates the role of FAS in antibacterial immunity in animals, which may indicate the relationship between the anabolism of fatty acids and immune responses in crustaceans. Highlights: Expression of LvFAS is up-regulated during V. parahaemolyticus infection. The promoter of LvFAS is regulated by NF-κB family proteins. Knockdown of LvFAS increases the mortality of V. parahaemolyticus infected shrimp. LvFAS influences expression of multiple immune-responsive genes.